Production and Properties of Isocyanate-Bonded MDF Manufactured from Acacia Mangium - Pensook, Suwanna (1990)
Medium density fiberboards (MDF) were manufactured from fast-growing Acacia mangium wood. The boards were produced at two levels of density, 600 and 750 kg/m³. Isocyanate and urea- formaldehyde resin adhesives were used asbinders. The physical, mechanical and dimensional stability properties were determined according to JIS 5906. Both adhesive and density affect significantly the properties of boards tested. It was found that the higher the density, the better the quality of the boards. Isocyanate bonded boards showed higher strength and more stable than urea - formaldehyde bonded boards, even when used at lower percentage of resins, 3 % and 13 %, respectively. It was also found that isocyanate bonded boards at low density had properties meeting the Japanese Industrial Standard, JIS 5906, Type-150 board whereas at high density (750 kg/m³), the boards met the Type-200. The properties of urea-formaldehyde bonded MDF also met JIS Type-150 for the lower density and Type-200 for the high density boards, but MOR in wet condition failed the standard.